Osmotic dehydration effects on major and minor components of chestnut (Castanea sativa Mill.) slices - Delgado, Teresa (2017)
The effect of osmotic dehydration (OD) conditions (temperature, time and sucrose concentration) on some nutritional parameters, soluble sugars, organic acids, fatty acids and vitamin E composition of chestnut slices was studied. Temperature at 60 ºC and contact time of 7.5 h decreased significantly both protein (in 20 and 15%) and fat (in 25 and 20%) contents when compared to 30 ºC and contact time of 2.5 h, simultaneously with the incorporation of sugars from the osmotic medium. An increase in temperature from 30 to 60 ºC and contact time from 2.5 to 7.5 h also changed amylose percentage from 12 to 17 g/100 g of starch, suggesting modifications on starch conformation. Concerning organic acids, an increase in temperature from 30 to 60 º C induced thermal degradation of citric (54% of loss), malic (36% of loss) and ascorbic (23% of loss) acids. Temperature and sugar concentration did not affect significantly fat composition, particularly PUFA, the main fatty acid class, while contact times of 7.5 h led to the partial oxidation of linolenic acid (17% of loss when compared to 2.5 h). A 50% decrease was also observed on vitamin E content when temperature increased from 30 to 60 º C. Thus, OD might cause changes on the chemical composition of chestnut slices, requiring low temperature and contact times to avoid loss of important bioactive components such as x-3 fatty acids (ex. linolenic acid) and vitamin E.